FORMULASI DAN UJI EFEKTIVITAS SALEP EKSTRAK ETANOL DAUN MANGROVE (Rhizophora mucronata) TERHADAP PENYEMBUHAN LUKA SAYAT PADA MENCIT (Mus muscullus) - Wiwik, Wiwik Triyani; Irwandi, Irwandi; Hardia, Lukman (JURNAL ETNOFARMASI, 2024)
Mangrove (Rhizophora mucronata) contains flavonoids, saponins and tannins. Compounds contained in mangrove leaves have antiinflammatory, anti viral and antimicrobial activites. Based on the compound, mangrove (Rhizophora mucronata) can be used an ointment for cuts. This study aims to test the preparation ofmangrove leaf ethanol extract ointment on the healing of cuts in mice. The process of extracting mangrove leaves (Rhizophora mucronata) uses the maceration method. In testing the ointment preparations, organoleptic tests, homogeneity tests, pH tests, spreadability tests and viscosity tests were carried out. Testing the effectiveness of wound healing using 5 groups consisting of 3 mice. Each group was giffen different treatment, namale K- was given an ointment base, K+ was given betadine ointment, F1 was given an ointment with a concetration of 2,5%, F2 was given an ointment with a concentration of 5% and F3 was given an ointment with a concentration of 7,5%. The results showed that the ointment met the standard organoleptic test requirements, test homogeneity, pH test, spreadability test and viscosity test. Based on the results of the incision test on mice, the most effective ointment preparation was a preparation with a concentration of 5%